Авторот како препејувач и препејувачот како автор – за двете преобразби на поемата „Сердарот“ - Tasevska Hadji Boshkova, Iskra (Филолошки факултет „Блаже Конески“, 2013)
One of the main conditions to provide a thorough inquiry of the specifics connected with the role (and the relation) of the author, and verse translator in the literary work of art is the diverse methodological orientation. On the one hand, the phenomenological implications are obvious, and they treat the nature of art and culture in general, and on the other, the mistreatment of the contemporary postmodern researches that emanated from the surpass of structural and phenomenal explorations can lead to a complex (and incorrect) conclusions. According to this, the primary intent that directs this analysis is not light up through the necessary confrontation between insufficiently discussed literary and theoretical problems, but instead, it is focused on their foundation in appropriate context, which can lead to important results applicable in the broader aesthetic analysis. In order to achieve transparency, our investigation is foremost directed to the two authors/verse translators (Georgi Stalev, and Gligor Prlicev), whose artistic method in the poem “Serdarot” makes their comparison possible. The verse translation creates a place of modification between the two value contexts, and the specific existence-in-extinction of the being in the literary work of art underlines impossibility of author’s destruction, and diminution. It is obvious that aesthetics is in embryo, according to its categories.